Sosialisasi Kesadaran Akan Bahaya Narkoba Dan Penyalahgunaan Narkoba Melalui Pencegahan Di Kelurahan Sidorejo Hilir - Muhammad Suganda Triadi; Ahmad Afandi (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
Several factors can underlie problems such as unhealthy associations, having a sense of wanting to try things, and so on. Cases of drug use are no stranger to hearing, currently drug use is increasingly becoming among students, students, adults and even the elderly. This community service program aims to increase awareness of the dangers of drugs for students. In this activity the population taken was all MTs Islamiyah Medan students, but the sample in this activity was 20 students. The results of the trial to the community showed that the dangers of drugs can threaten the health and even the lives of those who use them, especially for the younger generation. Drugs have very bad side effects if they are misused by users, especially if someone is already addicted to and even addicted to using drugs, then the crime of drug trafficking must be given strict sanctions. If it is not dealt with in a manner that will increase the distribution of narcotics in every area. The methods used are socialization, lectures, questions and answers, and discussions. From this activity there is awareness among students about the dangers of drugs which are a global problem for now, so that they are aware of the effects of drugs.